2017
DOI: 10.1007/s12185-017-2345-7
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 inhibition ameliorates survival from graft-versus-host disease in an allogeneic murine marrow transplantation model

Abstract: Acute graft-versus-host disease (GVHD) is a major cause of morbidity and mortality in allogeneic hematopoietic cell transplantation (allo-HCT). Majority of the current immunosuppressive strategies targeting donor T cells to prevent or treat acute GVHD are only partially effective, and often require escalated immunosuppressive therapy. Recent studies have revealed that activation of antigen-presenting cells in the proinflammatory milieu is important for the priming and promotion of GVHD. This activation is medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Dysregulated innate immune cells are key players in GvHD pathogenesis by activating APCs in the pro-inflammatory milieu ( 16) and inhibition of inflammatory cytokine signaling could ameliorate GvHD severity in mice and humans (15). Aiming to further understand the role and contribution of innate immune cells in GvHD, Kobayashi et al performed gene expression profiling on monocytes from patients who experienced GvHD after allo-HCT (156). The investigators found increased expression of TGFb-activated kinase 1 (TAK1) and downstream signaling molecules, including TNFa, IL-6 and IL-1b, in monocytes from patients with GvHD compared to patients who did not experience GvHD after allo-HCT.…”
Section: Tgfb-activated Kinase 1 (Tak1)mentioning
confidence: 99%
See 3 more Smart Citations
“…Dysregulated innate immune cells are key players in GvHD pathogenesis by activating APCs in the pro-inflammatory milieu ( 16) and inhibition of inflammatory cytokine signaling could ameliorate GvHD severity in mice and humans (15). Aiming to further understand the role and contribution of innate immune cells in GvHD, Kobayashi et al performed gene expression profiling on monocytes from patients who experienced GvHD after allo-HCT (156). The investigators found increased expression of TGFb-activated kinase 1 (TAK1) and downstream signaling molecules, including TNFa, IL-6 and IL-1b, in monocytes from patients with GvHD compared to patients who did not experience GvHD after allo-HCT.…”
Section: Tgfb-activated Kinase 1 (Tak1)mentioning
confidence: 99%
“…extracellular signal-regulated kinase (ERK) and p38 in toll-like receptor (TLR) signaling (16). Based on its role in mediating inflammatory signaling, inhibition of TAK1 was hypothesized being a novel strategy to ameliorate GvHD severity by reducing pro-inflammatory signaling and T-cell alloreactivity (156).…”
Section: Tgfb-activated Kinase 1 (Tak1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Trim8 directly ubiquitinates transforming growth factor-beta-activated kinase 1, thus promoting its phosphorylation and activation of downstream c-Jun N-terminal kinase/p38 and NF-κB signalling [11]. The MAP3-kinase TGF-beta-activated kinase 1 (TAK1) critically modulates innate and adaptive immune responses and connects cytokine stimulation with activation of inflammatory signalling pathways, including cell survival, apoptosis, autophagy, oxidative processes, cancer and the immune response [27][28][29][30]. TAK1 is a MAP3K protein and is considered a common upstream molecule in the MKK-JNK/p38 and IKK-NF-κB cascade, which induces activation of downstream JNK and NF-κB signalling [31][32][33].…”
Section: The Effect Of Trim8 On Hepatic I/r Is Mediated By Tak1 Activitymentioning
confidence: 99%